Analisis Penerapan Arsitektur Sistem Informasi Terhadap Kinerja Layanan Sirkulasi Di Perpustakaan Universitas Nias Raya - Dachi, Fridayanti; Kristiani Ndruru, Fortin; Miahati Gohae, Margaret; Emanuel Maduwu, Gempa (Jurnal Sistem Informasi Galuh, 2025)
This study aims to determine the effect of implementing information systems architecture, in this case the SLiMS (Senayan Library Management System) V9.6.1 application on improving circulation services at the Nias Raya University Library. With descriptive qualitative methods, data was collected through observation, interviews, and documentation. The results showed that since the implementation of SLiMS V9.6.1 in 2021, there has been a significant increase in the efficiency of circulation services, easy access to collection information, and library data management. Nevertheless, some obstacles such as dependence on internet connection and the e-book upload process that requires additional applications are still a challenge. This research also compares service conditions before and after the implementation of SLiMS V9.6.1, and provides recommendations for system optimization.